A STUDY ON THE JUNIOR HIGH SCHOOL STUDENTS’ SPATIAL ABILITY AND MATHEMATICS PROBLEM SOLVING IN MOJOKERTO - Putri, Rizky Oktaviana Eko (PEOPLE: International Journal of Social Sciences, 2020)
The aim of this study was to investigate the spatial ability the relation of spatial ability and geometrical problem-solving ability of junior high school students in Mojokerto, Indonesia. Data in this descriptive study was collected using The Purdue Spatial Visualization Test (PSVT). PSVT was used to analyze students’ rotation spatial skills element then categorized into three different spatial ability groups (High, Intermediate, and Low). The mathematics problem-solving data were collected by giving mathematical ability written test to the students. Results showed that more than 70% of participants possessed intermediate level both in spatial and problem-solving ability. Furthermore, the statistics result indicated a positive correlation between spatial ability and geometrical problem-solving ability. Qualitative analysis revealed that students had difficulty in solving the problem of spatial rotation especially students in low-level ability. Finally, significant evident recommend spatial ability need to be considered involved in the learning activity.